"Avløypet" og "Avløysa/Avløysinga" – same tanke på to måtar, med dialektflytting? - Eldar Heide (Namn og Nemne)
This article examines the West Norwegian place name Avløypet alongside the West, Mid, and North Norwegian names Avløysa/ Avløsa/Avløysinga/Avløysingen, which describe similar types of terrain. These names likely stem from a shared concept, making interpretation simpler. Coastal communities historically observed that many small islets and rocks appear just barely separated from the mainland, leading to place names that reflected this image. In much of Western Norway, the islet was seen as “peeled” (løypt) from the land, while further north, it was viewed as “loosened” (løyst). The distribution of Avløysa in Northern Norway suggests it was borrowed from southern areas in the Early Modern period, likely via fisheries in Lofoten and then Eastern Finnmark. Variants like Avløysinga may have spread with emigrants from northern Western Norway to Troms and Western Finnmark, explaining certain dialect features in these areas.